THE IMPACT OF INDONESIAN FILM TOWARDS PROMOTING RANU KUMBOLO LAKE IN EAST JAVA, INDONESIA - Hoorina, Jessica; Soeprapto, Vishnuvardhana (Academic Research Centre Services, 2015)
A phenomenon called film-induced tourism which lately been increasing the amount of visitor towards a destination that appear through a movie. Watching movie is an intangible visual experience, but it could be change into an actual experience by visiting the film locations. It will give tourist an involvement and recreate their own feeling by experiencing themselves into a destination. In this research, evaluate the correlation of film-induced tourism towards the effectiveness of promotional destination tool. By using a novel-based movie from Indonesia, ?5 Cm? movie and Ranu Kumbolo Lake, which is located in Mount Semeru in East Java, Indonesia; as the location which will be promoted as the result of watching ?5 Cm? movie. The research methods will be using quantitative data and also questionnaires as research techniques. This research shows a strong relationship between film-induced tourism and the effectiveness of promotional destination tool, which shown by Structural Equation Modeling (SEM).